A Rare Case of Diprosopus Buffalo Calf in a Non-Descript Buffalo - Malik, Asloob Ahmad; Habib, Rayees; Dar, Ishtiyaq Ahmad; Malik, Faisal Ahmad (The Indian Journal of Animal Reproduction, 2022)
A case of diprosopus monauchenos is described in a non-descript buffalo. A 6 year old buffalo with single parity was presented along with a live defective male calf was presented to the clinic.  The congenital defective male calf was delivered normally by the dam. The major gross anatomical malformations were restricted to the head only. Physical examination revealed two oral cavities and both of them fused medially forming a single epiglottis and oesophagus. The male calf survived only for a week on hand-feeding of milk. This is the first diprosopus case report in buffalo calf from Jammu and Kashmir, India
Keywords: Diprosopus; Non-descript buffalo; buffalo calf; Dystocia